Efficacy and safety of intravenous acetaminophen (2 g/day) for reducing opioid consumption in Chinese adults after elective orthopedic surgery: A multicenter randomized controlled trial - Yin, Feng; Ma, Wei; Liu, Qiao; Xiong, Liu-Lin; Wang, Ting-Hua; Li, Qian; Liu, Fei (Frontiers in Pharmacology, 2022)
Background Acetaminophen is an important component of a multimodal analgesia strategy to reduce opioid consumption and pain intensity after an orthopedic surgery. The opioid-sparing efficacy of intravenous acetaminophen has been established at a daily dose of 4 grams. However, it is still unclear for the daily dose of 2 grams of acetaminophen, which is recommended by the China Food and Drug Administration Center for Drug Evaluation, in terms of its efficacy and safety. Objectives This study aimed to evaluate the efficacy and safety of intravenous acetaminophen at a daily dose of 2 grams for reducing opioid consumption and pain intensity after orthopedic surgery. Methods In this multicenter, randomized, double-blind, placebo-controlled phase III trial, 235 patients who underwent orthopedic surgery were randomly assigned to receive intravenous acetaminophen 500 mg every 6 hours or placebo. Postoperative morphine consumption, pain intensity at rest and during movement, and adverse events were analysed. Results For the mean (standard deviation) morphine consumption within 24 h after surgery, intravenous acetaminophen was superior to placebo both in the modified intention-to-treat analysis [8.7 (7.7) mg vs 11.2 (9.2) mg] in the acetaminophen group and the placebo group, respectively. Difference in means: 2.5 mg; 95% confidence interval, 0.25 to 4.61; P = 0.030), and in the per-protocol analysis (8.3 (7.0) mg and 11.7 (9.9) mg in the acetaminophen group and the placebo group, respectively. Difference in means: 3.4 mg; 95% confidence interval: 1.05 to 5.77; P = 0.005). The two groups did not differ significantly in terms of pain intensity and adverse events. Conclusions Our results suggest that intravenous acetaminophen at a daily dose of 2 grams can reduce morphine consumption by Chinese adults within the first 24 h after orthopedic surgery, but the extent of reduction is not clinically relevant.